Перспективи використання алгоритмів штучного інтелекту для прогнозування та відстеження побічних ефектів лікарських засобів - Швиденко, А. О. (ХНУРЕ, 2024)
This work studies the use of artificial intelligence (AI) algorithms for predicting and monitoring the side effects of medicinal drugs. The first algorithm considers the use of a Geometric Self Expressive Model (GSEM) with data from the SIDER and OFFSIDES databases. In GSEM, the focus is on a matrix approach to predict the likelihood of drug side effects. It is also proposed to use the AI algorithm in post-clinical observation and in collecting patient data from social networks and forums for discussion. This research demonstrates the potential of AI as a complement to traditional methods with the aim of enhancing the safety of medical treatment.
Keywords: побічний ефект лікарських засобів; лікарський засіб